Overview Of Msme Owners' Perception Of The Necessity Of Financial Reports And Influencing Factors - Devy, Tartila (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study aims to determine how the owner perception of micro, small and medium enterprises (MSMEs) in Bukittinggi, regarding the presentation of financial statements based on the EMKM Financial Accounting Standards. and identify the factors influence presentation of financial statements based on SAK EMKM. This research used a qualitative approach, focusing on MSMEs in Bukittinggi, where 408 registered industrial companies have permits. To enhance the response rate and minimize bias, the study targeted MSMEs likely to return questionnaires promptly. The results of the study state that none of educational background, business age, business size, information and socialization affect financial report preparation. Many MSMEs stakeholders perceive them as unimportant, viewing the preparation of such reports as a waste of both time and resources. Additionally, financial reporting is often seen as too complex to be applied effectively in small and medium-sized businesses. MSME owners are more focused on increasing their sales revenue, making it difficult for them to allocate time to review financial statements. Instead, they place greater value on experience and traditional practices passed down through generations in managing their businesses